Assessment of interprofessional collaboration before and after a simulated disaster drill experience. (August 2019) - Digregorio, Heiddy; Graber, Jennifer S.; Saylor, Jennifer; Ness, Michelle
Abstract: Introduction: With increasing acuity, patient care requires a collaborative approach by a team of providers. Recent literature indicates healthcare professionals lack the ability to work in collaboration with other healthcare professionals resulting from communication and collaborative practice gaps. Background/Literature: Disasters require a rich collaboration of teams in order to be effective. As a result, interprofessional collaboration is a foundational underpinning of disaster preparedness. The overall purpose of this study was to assess perceptions of interprofessional collaboration before and after participating in an interprofessional simulated disaster drill as part of a Community Health Nursing course. Methods: This pre-test, post-test descriptive research design assessed communication, collaboration, roles/responsibilities, patient focus, team functioning and conflict management of nursing students who participated in a simulated disaster drill. Data/Results: Participants were nursing majors and primarily Caucasian females (n = 50, 89% and n = 56, 97% respectively), representative of the school of nursing population at the University. Wilcoxon Signed-Ranks test indicated that scores for the total ICAR post-test were significantly lower than the Total ICAR pre-test (Z = −2.006, p = .045, r = −0.19). While each of the individual sections of the ICAR had a lower mean score on the ICAR post-test as compared to the pre-test, collaborative patient/client-family centered approach was statistically significant (p = 0, 0.002). Discussion: Following the simulated disaster drill experience, nursing students identified gaps in communication, collaboration, roles and responsibilities, collaborative patient/client-family centered approach, team functioning, conflict management/resolution. Conclusions: The study assessed the perceptions of interprofessional collaboration among undergraduate nursing students before and after a simulated disaster drill. The assessment identified the need to integrate interprofessional competencies in disaster preparedness education.